Ectopic Endometrial Cell-Derived Exosomal Moesin Induces Eutopic Endometrial Cell Migration, Enhances Angiogenesis and Cytosolic Inflammation in Lesions Contributes to Endometriosis Progression - Abudula, Maidinaimu; Fan, Xiaodan; Zhang, Jing; Li, Jiajie; Zhou, Xiaoming; Chen, Yichen (Frontiers in Cell and Developmental Biology, 2022)
Background: Endometriosis (EMs) is the most common gynaecological disorder with its etiology and/or pathophysiology remains enigmatic. Recent studies showed that extracellular vesicles (EVs), exosomes in particular, play a critical role in developing various clinical disorders. However, the implication of exosomes in endometriosis progression has not been well elucidated. Method: The ectopic stromal cellular exosomes (eEVs) were assessed by transwell assay, scratch tests, tube formation assay, western blot, and qRT-PCR analysis. Protein expression profiles of exosomes in endometrial tissue and vaginal discharge collected from patients with EMS and healthy donors were analysed by Mass spectrometry. siRNA interference technology was used to inhibit the expression of exosomal protein for the functional analysis in in-vivo. Finally, in-vitro experiments were performed to validate the results that we observed in EMs mouse model. Results: In vitro, we discovered that eEVs improved NSC migratory potential by upregulating MMP9 expression and activity. eEVs also aided angiogenesis and elevated the expression of inflammatory cytokines in ovarian epithelial cells, according to our findings. Moesin (MSN) levels in ESC exosomes were substantially greater than in NSC exosomes(1.22e8±5.58e6 vs. 6.605e7±4.574e6, LFQ intensity), as shown by protein mass spectrometry and bioinformatics analysis. In ectopic stromal cells, ERa receptors stimulated the RhoA/Rock-2/MSN pathway. We discovered that downregulating exosomal moesin reduced NSC migration (about 3-fold change) and MM9 expression (about 2-fold change). On the other hand, Exomsni inhibited angiogenesis and inflammatory cytokine release. In vivo, the result of immunohistochemistry and immunofluorescence demonstrated that exosomal MSN substantially modified the expression of MM9, VEGFR and p-VEGFR in polyclonal lesions. In addition, we discovered an elevation in the expression of proinflammatory factors in the surrounding tissue. Conclusion: Exosomal MSN derived from ectopic stromal cells can contribute to endometriosis progression by mediating the construction of a “migration-vascularization-inflammation” loop in the ectopic environment.